INSPIRACJE GRECKO-RZYMSKIE W IDEOLOGII NAZISTOWSKIEJ - Chiżyńska, Katarzyna (Collectanea Philologica, 2013)
The paper focuses on ancient ideas, myths and texts, which has been adapted by Third Reich in order to build Nazi ideology. Hitler’s followers passionately read works of Plato, Plutarch and Tacitus, however, their intention was not to learn about antiquity, but to fit ancient thoughts to National Socialism. The same thing NSDAP tried to do with ancient art, architecture, gestures (Roman salute) and symbols (swastika). Führer’s attitude towards Greek and Roman antiquity was very complex. Psychological term to name this ambiguous relationship is “double-bind”.